Strategi Kepemimpinan dan Inovasi Manajerial dalam Meningkatkan Kualitas Pelayanan Rumah Sakit Tipe C - Susmita Aini; Sukamto (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This article is a literature review that systematically examines leadership strategies and managerial innovation applied in type C hospitals, with the aim of identifying effective approaches in improving the quality of health services. Type C hospitals as medium-level health facilities have an important role in the referral service system, but often face challenges in the management and provision of quality services. Therefore, strengthening leadership and innovation aspects is crucial to answer the need for sustainable service reform. This study uses a systematic literature review method by analyzing national and international scientific publications published in the 2020–2025 time frame. The focus of the study was directed to the themes of transformational leadership, managerial innovation, and service quality of type C hospitals. The results of the study show that transformational leadership has a strategic role in shaping an innovative and collaborative organizational culture. This leadership style encourages changes in organizational behavior, increased motivation of health workers, and openness to digital transformation. Managerial innovations, especially in the form of digitizing services and strengthening health information systems, have been proven to improve operational efficiency, medical data accuracy, and patient satisfaction. The synergy between visionary leadership and planned managerial innovation creates an adaptive and quality-oriented healthcare ecosystem. However, the implementation of this strategy still faces obstacles in the form of resistance to change, limited resources, and low digital literacy among health workers. Therefore, managerial commitment, human resource capacity development, and consistent policy support are needed to ensure the sustainability of healthcare transformation in type C hospitals.